MOF (Metal Organic Framework) material based on Au-coated CuS modification as well as preparation method and application of MOF material
Through the physical composite of Au@CuS modified MOF material and Cu-MOF, Au@CuS@Cu-MOF composite gas sensitive material was prepared for use in QCM gas sensors, which solved the problem of insufficient performance of existing ammonia sensor materials. Achieve ammonia detection effect with high sensitivity, fast response and good mechanical properties.
Patent Information
- Application Number
- CN202411624017.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
Existing ammonia sensor materials have problems such as poor sensitivity, long response time, poor mechanical properties, poor selectivity, low repeatability, high working temperature and poor chemical stability, which are difficult to meet the needs of high-performance ammonia detection.
The Au@CuS modified MOF material is used as the gas-sensitive material. By physically combining Au@CuS with Cu-MOF, Au@CuS@Cu-MOF composite gas-sensitive material is prepared and used in QCM gas sensors. Near infrared light is used to activate the photothermal effect to improve the ammonia detection performance.
It significantly improves the sensitivity and response speed of the QCM gas sensor to ammonia, shortens the recovery time, improves the mechanical properties and repeatability of the material, and improves the selectivity of ammonia.
Smart Images

Figure CN119425639A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas-sensitive materials, and in particular to an Au@CuS-modified MOF material and a preparation method and application thereof. Background Art
[0002] Ammonia (NH3) is a colorless gas with a strong pungent odor. It is widely used in many fields such as industrial production, agricultural production, environmental protection and daily life. Ammonia is highly irritating to the human body and can burn the skin, eyes and respiratory mucous membranes. Inhalation can damage liver function and reduce the body's immunity, inducing various diseases. In addition, excessive release of ammonia in the environment can also lead to eutrophication of soil and water bodies. Therefore, the development of high-performance ammonia sensors is of great practical significance.
[0003] Quartz Crystal Microbalance (QCM) gas sensor has attracted wide attention due to its advantages such as high sensitivity, simple structure, room temperature operation, real-time online detection and low cost. This gas sensor is a new type of gas detection device based on the high sensitivity of piezoelectric quartz wafer to mass changes. QCM gas sensor uses a sensitive film modified on the surface of quartz wafer to capture the gas to be measured. When the sensitive film adsorbs the gas, it will cause the frequency of the quartz crystal to change. By measuring this change, the gas to be measured can be detected. It can be seen that the sensing material (gas-sensitive material) that constitutes the sensitive film is the key to QCM detection of ammonia.
[0004] At present, a variety of materials have been used to prepare QCM ammonia sensors, such as polyvinyl acetate (PVAc) nanofibers, polyaniline / titanium dioxide (PANI / TiO2) and polypyrrole / titanium dioxide (PPy / TiO2) composites, graphene / titanium dioxide (GO / TiO2) composites, cellulose acetate (CA) electrospun nanofiber membranes, and some metal oxides. Although these materials have their own advantages, they also face some disadvantages, such as the complex preparation process and high cost of materials such as PVAc nanofibers and graphene, the poor structural adjustability of inorganic materials (such as TiO2) and generally require a high working temperature and excessive energy consumption, and the single metal organic framework material (MOFs) material as a gas-sensitive material has poor sensitivity, long response time and poor mechanical properties. Some materials have a long response and recovery time to ammonia, which makes the detection process time-consuming, and there are problems such as poor selectivity, low repeatability, high working temperature and poor chemical stability. Therefore, it is of great significance to develop new ammonia sensing materials. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a MOF material modified based on Au@CuS and a preparation method and application thereof.
[0006] The above object of the present invention is achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a MOF material modified by Au@CuS, comprising the following steps:
[0008] Au@CuS is dispersed in an organic solvent to obtain an Au@CuS dispersion; MOF and a surfactant are dissolved in an organic solvent to obtain a MOF solution; the Au@CuS dispersion is mixed with the MOF solution, wherein the mass ratio of Au@CuS in the Au@CuS dispersion to MOF in the MOF solution is (2-15):100, to obtain the MOF material modified based on Au@CuS.
[0009] MOFs materials have the advantages of highly controllable pore structure, huge specific surface area, diverse functionalization strategies and good stability. CuS nanomaterials have a plasma effect and have significant photothermal conversion efficiency under near-infrared light, showing potential application prospects in photothermal therapy. Au nanoparticles are combined with CuS to form a heterostructure, which provides higher photothermal conversion efficiency through local electromagnetic enhancement and greater radiation dose deposition, as well as the generation of active oxygen species. The MOF material modified by Au@CuS in the present invention can be used to prepare QCM gas sensors. The photothermal effect generated by Au@CuS will promote the adsorption of gas by MOFs materials, thereby improving the gas detection performance of the sensor, such as sensitivity and response recovery time.
[0010] Furthermore, the concentration of the Au@CuS dispersion is 0.005-0.05 g / mL, and the concentration of the MOF solution is 0.005-0.05 g / mL.
[0011] Furthermore, the volume ratio of the Au@CuS dispersion to the MOF solution is (2-15):100.
[0012] Furthermore, the MOF may be Cu-BTC, MOF-808(Zr), Cu(cyhdc), etc.
[0013] Furthermore, the MOF is preferably a copper-based MOF (Cu-MOF), and more preferably Cu(cyhdc).
[0014] Furthermore, the mass ratio of the MOF to the surfactant is (0.5-2):1.
[0015] Furthermore, the organic solvent is selected from one or more of methanol, ethanol and N,N-dimethylformamide (DMF).
[0016] Furthermore, the surfactant is selected from one or more of polyvinyl pyrrolidone (PVP), polyethylene glycol fatty acid ester and polyacrylamide (PAM).
[0017] Furthermore, the preparation method of Au@CuS comprises the following steps: dissolving copper salt and surfactant in water, adding alkali, hydrazine hydrate and sulfide salt in sequence, and reacting at 60-75°C to obtain CuS nanospheres; dissolving the CuS nanospheres and surfactant in an organic solvent, adding tetrachloroauric acid and a reducing agent to obtain the Au@CuS.
[0018] Furthermore, the copper salt is CuSO4·5H2O or CuCl2·2H2O, the surfactant is PVP, the base is NaOH or KOH, the sulfide salt is Na2S·9H2O, and the reducing agent is NaBH4.
[0019] Furthermore, the preparation method of the Cu(cyhdc) comprises the following steps: dissolving a copper salt and trans-1,4-cyclohexanedicarboxylic acid in an organic solvent, and reacting at 85-95° C. to obtain the Cu(cyhdc).
[0020] Furthermore, the copper salt is Cu(NO3)2·2.5H2O or CuCl2·2H2O, and the organic solvent is N,N'-dimethylformamide (DMF).
[0021] Furthermore, the mass ratio of the copper salt to trans-1,4-cyclohexanedicarboxylic acid is (2-3):(1.5-2).
[0022] Furthermore, the reaction time is 15-17h.
[0023] In a specific embodiment, copper salt and trans-1,4-cyclohexanedicarboxylic acid are dissolved in an organic solvent, reacted at 85-95° C. for 15-17 hours, cooled to room temperature, centrifuged, washed, and dried to obtain a copper-based MOF.
[0024] Furthermore, the mixing further includes the steps of centrifugation and washing.
[0025] The second aspect of the present invention provides a MOF material based on Au@CuS modification prepared by the method described in the first aspect.
[0026] The third aspect of the present invention provides an application of the Au@CuS-modified MOF material described in the second aspect, wherein the Au@CuS-modified MOF material is used as a gas-sensitive material to prepare a QCM gas sensor, especially a QCM ammonia sensor.
[0027] The fourth aspect of the present invention provides a QCM gas sensor, comprising the Au@CuS-modified MOF material described in the second aspect.
[0028] In a specific embodiment, the Au@CuS modified MOF material dispersion is coated on the substrate of the QCM gas sensor.
[0029] Furthermore, the concentration of the Au@CuS modified MOF material dispersion is 1-5 mg / mL.
[0030] The fifth aspect of the present invention provides application of the QCM gas sensor described in the fourth aspect in detecting ammonia.
[0031] Under near-infrared irradiation at 980nm, the Au@CuS-modified MOF material as a gas-sensitive material exhibits an efficient photothermal effect, significantly improving the sensitivity and response speed of the QCM gas sensor to ammonia and greatly reducing the recovery time.
[0032] Beneficial effects of the present invention:
[0033] The present invention synthesizes a copper-based MOF material (Cu-MOF) with simple synthesis, low cost and high selective adsorption of ammonia. Au@CuS and Cu-MOF are physically compounded under the action of a surfactant to obtain a MOF material modified by Au@CuS with strong mechanical properties, namely, Au@CuS@Cu-MOF composite gas-sensitive material. Compounding Cu-MOF and Au@CuS to prepare a QCM gas sensor and irradiating it with infrared light can greatly improve the detection performance of Cu-MOF for ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The morphology characterization diagram of Au@CuS@Cu-MOF prepared in Example 1; wherein, (a) is a scanning electron microscope image, (b) is a transmission electron microscope dark field image, (c) is a C element distribution diagram, (d) is a Cu element distribution diagram, (e) is a S element distribution diagram, and (f) is an Au element distribution diagram.
[0035] Figure 2 This is a performance comparison chart of the QCM gas sensor prepared by Cu-MOF and Au@CuS@Cu-MOF of Examples 1-4 for detecting NH3.
[0036] Figure 3It is a comparison chart of the detection performance of different QCM gas sensors for NH3 at 40% RH; wherein, (a) is the response recovery curve of the QCM gas sensor prepared by Cu-MOF to 10-500ppm NH3, (b) is the response recovery curve of the QCM gas sensor prepared by Au@CuS@Cu-MOF in Example 3 to 10-500ppm NH3, and (c) is the response recovery curve of the QCM gas sensor prepared by Au@CuS@Cu-MOF in Example 3 to 10-500ppm NH3 under 980nm infrared light irradiation.
[0037] Figure 4 It is a comparison chart of the detection performance of different QCM gas sensors for NH3 at 80% RH; wherein, (a) is the response recovery curve of the QCM gas sensor prepared by Cu-MOF to 10-500ppm NH3, (b) is the response recovery curve of the QCM gas sensor prepared by Au@CuS@Cu-MOF in Example 3 to 10-500ppm NH3, and (c) is the response recovery curve of the QCM gas sensor prepared by Au@CuS@Cu-MOF in Example 3 to 10-500ppm NH3 under 980nm infrared light irradiation.
[0038] Figure 5 The following is a comparison of the response performance of different QCM gas sensors to 10-500ppm NH3 under two humidity conditions; (a) is 40% RH and (b) is 80% RH.
[0039] Figure 6 The response recovery time comparison chart of different QCM gas sensors to 50ppm NH3 at 80% RH; wherein, (a) is the QCM gas sensor prepared by Cu-MOF, (b) is the QCM gas sensor prepared by Au@CuS@Cu-MOF of Example 3, and (c) is the QCM gas sensor prepared by Au@CuS@Cu-MOF of Example 3 under 980nm infrared light irradiation.
[0040] Figure 7 The repeatability curves of different QCM gas sensors detecting 50ppm NH3 at 80% RH; among them, (a) is the QCM gas sensor prepared by Cu-MOF, (b) is the QCM gas sensor prepared by Au@CuS@Cu-MOF in Example 3, and (c) is the QCM gas sensor prepared by Au@CuS@Cu-MOF in Example 3 under 980nm infrared light irradiation.
[0041] Figure 8Surface temperature diagrams of different QCM gas sensors; (a) is the temperature of the blank substrate, (b) is the temperature of the substrate when loaded with Au@CuS@Cu-MOF, and (c) is the temperature of the substrate after loading with Au@CuS@Cu-MOF and stabilizing with 980nm infrared light irradiation. DETAILED DESCRIPTION
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0043] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0044] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0045] In the following examples, Cu-MOF refers to Cu(cyhdc).
[0046] Example 1
[0047] A method for preparing a MOF material (Au@CuS@Cu-MOF) modified by Au@CuS comprises the following steps:
[0048] 0.1 g Au@CuS was dispersed in 10 mL methanol to obtain Au@CuS dispersion; 0.1 g Cu-MOF and 0.1 g PVP were dissolved in 10 mL methanol to obtain Cu-MOF solution; 20 uL Au@CuS dispersion was mixed with 1 mL Cu-MOF solution, stirred at room temperature for 10 min, the product was collected by centrifugation, and washed with methanol 3 times to obtain Au@CuS@Cu-MOF, recorded as CuS-1.
[0049] Among them, Au@CuS was prepared by the following method: 0.025g CuSO4·5H2O and 0.4g PVP were dissolved in 50mL deionized water. After magnetic stirring at room temperature for 10 minutes, 50mL 0.1mmol / L NaOH solution was added, and 80μL hydrazine hydrate (80%) solution was added dropwise while stirring continuously to obtain a yellow suspension. Then 0.4g Na2S·9H2O was added to the solution, and the solution immediately turned dark brown. The mixture was transferred to a flask and heated in an oil bath at 70℃ with stirring for 1.5 hours. The CuS nanospheres were separated by centrifugation and washed four times with ethanol and deionized water. The dried CuS was dissolved in 40mL ethanol containing 0.2g PVP and stirred continuously for 1 hour, and then 96μL HAuCl4·3H2O solution (0.1g / mL) was added. 0.0113g NaBH4 was dissolved in 100mL ethanol to obtain a NaBH4 solution. Then, 10 mL of NaBH4 solution was added to the previous mixture and magnetically stirred for 30 min. The product was centrifuged and washed three times with ethanol. Finally, the obtained Au@CuS nanospheres were dried at room temperature.
[0050] Cu-MOF was prepared by the following method: 2.326g Cu(NO3)2·2.5H2O and 1.722g trans-1,4-cyclohexanedicarboxylic acid were dissolved in 100mL N,N'-dimethylformamide (DMF), and the mixture was added to a 250mL blue-capped bottle and placed in a 90℃ oven for 16 hours. The blue-capped bottle was taken out, cooled to room temperature, and the blue crystals were separated by centrifugation, washed three times with DMF and methanol, and finally dried in a 60℃ oven for 5 hours.
[0051] The morphology of Au@CuS@Cu-MOF was characterized. Figure 1 As can be seen in (a) and (b), Au@CuS@Cu-MOF mainly appears as spherical nanoparticles and nanorod structures; Figure 1 (c)-(f) show that S and Au elements are mainly distributed in the spherical particle area, while Cu is distributed in the entire sample, and its distribution is more obvious at the particles. This indicates that the Cu-MOF in the sample is a nanorod structure, and the CuS nanoparticles loaded with Au are tightly attached to the Cu-MOF surface, and Au is mainly distributed on the CuS surface.
[0052] Example 2
[0053] A method for preparing a MOF material (Au@CuS@Cu-MOF) modified by Au@CuS is basically the same as that in Example 1, except that 50 uL of Au@CuS dispersion was mixed with 1 mL of Cu-MOF solution, stirred at room temperature for 10 min, the product was collected by centrifugation, and washed with methanol three times to obtain Au@CuS@Cu-MOF, which was recorded as CuS-2.
[0054] Example 3
[0055] A method for preparing a MOF material (Au@CuS@Cu-MOF) modified by Au@CuS is basically the same as that in Example 1, except that 100 uL of Au@CuS dispersion was mixed with 1 mL of Cu-MOF solution, stirred at room temperature for 10 min, the product was collected by centrifugation, and washed three times with methanol to obtain Au@CuS@Cu-MOF, which was recorded as CuS-3.
[0056] Example 4
[0057] A method for preparing a MOF material (Au@CuS@Cu-MOF) modified by Au@CuS is basically the same as that in Example 1, except that 150 uL of Au@CuS dispersion was mixed with 1 mL of Cu-MOF solution, stirred at room temperature for 10 min, the product was collected by centrifugation, and washed with methanol three times to obtain Au@CuS@Cu-MOF, which was recorded as CuS-4.
[0058] Application Examples
[0059] The substrate of the QCM gas sensor was cleaned with ethanol and deionized water, and the cleaned substrate was fixed on a horizontal plane. The Au@CuS@Cu-MOF prepared in Example 1-4 was dispersed in methanol to prepare a 1 mg / mL Au@CuS@Cu-MOF dispersion. 3.5 μL of the Au@CuS@Cu-MOF dispersion was dropped on the center of the QCM substrate and dried at room temperature for 2 hours.
[0060] Test Case
[0061] The QCM gas sensor prepared in the application example is used to detect ammonia. The detection method is as follows:
[0062] Place the QCM gas sensor in the air cavity and connect it to the oscillator circuit and frequency counter. Turn on the oscillator circuit and frequency counter, and after the device is preheated for 10 minutes, introduce background gas (N2 with a certain humidity) and start measuring the frequency change of the QCM gas sensor. When the baseline frequency is stable, the flowmeter controls the introduction of the gas to be tested (ammonia with a certain concentration, nitrogen as the background gas, and the same humidity). After 300 seconds, introduce the background gas and then switch to the next concentration, thereby obtaining the response recovery curve of the QCM gas sensor.
[0063] The performance of the QCM gas sensor prepared by Cu-MOF and Au@CuS@Cu-MOF of Examples 1-4 in detecting NH3 was compared. The response to 50ppm NH3 at 80% humidity (RH) was tested. The test results are as follows: Figure 2 As shown in the figure, under 80% RH conditions, the QCM gas sensor prepared by Cu-MOF has the worst response to 50ppm NH3. With the increase of Au@CuS modification amount, the response ability of QCM gas sensor to ammonia first increases and then weakens.
[0064] The detection performance of different QCM gas sensors for 10-500ppm NH3 was studied at 40% RH. Figure 3 As shown in (a) and (b), compared with Cu-MOF, Au@CuS@Cu-MOF has a slightly improved response to ammonia. This may be due to the fact that Au@CuS has a certain adsorption performance for ammonia. When the ammonia concentration is 50ppm, the response increases from 13Hz to 25Hz, and the sensitivity increases from 0.26Hz / ppm to 0.50Hz / ppm. Figure 3 As shown in (c), during the ammonia detection process, 980nm infrared light irradiation was carried out, and the responsiveness of Au@CuS@Cu-MOF to ammonia was greatly improved. When the ammonia concentration was 50ppm, the response reached 32Hz and the sensitivity reached 0.64Hz / ppm.
[0065] The detection performance of different QCM gas sensors for 10-500ppm NH3 was studied at 80% RH. Figure 4 As shown in (a) and (b), compared with Cu-MOF, Au@CuS@Cu-MOF has better response to ammonia. When the ammonia concentration is 50ppm, the response increases from 91Hz to 137Hz, and the sensitivity increases from 1.82Hz / ppm to 2.74Hz / ppm. Figure 4As shown in (c), during the ammonia detection process, 980nm infrared light irradiation was performed, and the responsiveness of Au@CuS@Cu-MOF to ammonia was significantly improved. When the ammonia concentration was 50ppm, the response reached 166Hz and the sensitivity reached 3.32Hz / ppm.
[0066] The response performance of different QCM gas sensors to 10-500ppm NH3 under the above two humidity conditions was compared. Figure 5 As shown, when detecting under different humidity conditions, the QCM gas sensor constructed by Au@CuS@Cu-MOF was irradiated with 980nm infrared light, and its response performance to ammonia was the best, and with the increase of humidity, the response performance of the sensor also improved.
[0067] The response recovery time of different QCM gas sensors to 50ppm NH3 at 80% RH was compared. Figure 6 As shown in the figure, the response and recovery time of Cu-MOF are 201s and 257s, respectively, while the response and recovery time of Au@CuS@Cu-MOF are significantly shortened, 161s and 203s, respectively. When Au@CuS@Cu-MOF is irradiated with 980nm infrared light, its response and recovery time are greatly shortened to 84s and 43s, respectively, indicating that the photothermal effect of Au@CuS has a great influence on the performance of the QCM gas sensor.
[0068] The repeatability of different QCM gas sensors for detecting 50ppm NH3 at 80% RH was studied. Figure 7 As shown in the figure, the repeatability of Cu-MOF and Au@CuS@Cu-MOF is poor. When irradiated with 980nm infrared light, the repeatability of the QCM gas sensor is greatly improved, which is mainly due to the thermal effect promoting the release of adsorbed ammonia.
[0069] In order to study the thermal effect of Au@CuS@Cu-MOF composites, the surface temperature of different QCM gas sensor substrates was studied. Figure 8 As shown in the figure, the temperature of the blank substrate and the substrate loaded with Au@CuS@Cu-MOF is relatively low. After irradiation with 980nm infrared light, the temperature of the substrate has been greatly increased. Therefore, the infrared light induces a significant photothermal effect of the material, thereby increasing the device temperature, which is the main reason for the enhanced performance of the QCM gas sensor.
[0070] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a MOF material modified by Au@CuS, characterized in that: The following steps are involved: Au@CuS is dispersed in an organic solvent to obtain an Au@CuS dispersion; MOF and a surfactant are dissolved in an organic solvent to obtain a MOF solution; the Au@CuS dispersion is mixed with the MOF solution, wherein the mass ratio of Au@CuS in the Au@CuS dispersion to MOF in the MOF solution is (2-15):100, to obtain the MOF material modified based on Au@CuS.
2. The preparation method according to claim 1, characterized in that: The MOF is a copper-based MOF.
3. The preparation method according to claim 1, characterized in that: The preparation method of the copper-based MOF comprises the following steps: dissolving a copper salt and trans-1,4-cyclohexanedicarboxylic acid in an organic solvent, and reacting at 85-95° C. to obtain the copper-based MOF.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the MOF to the surfactant is (0.5-2):
1.
5. The preparation method according to claim 1, characterized in that: The preparation method of Au@CuS comprises the following steps: dissolving copper salt and surfactant in water, adding alkali, hydrazine hydrate and sulfide salt in sequence, and reacting at 60-75°C to obtain CuS nanospheres; dissolving the CuS nanospheres and surfactant in an organic solvent, adding tetrachloroauric acid and a reducing agent to obtain the Au@CuS.
6. A MOF material modified by Au@CuS prepared by the method according to any one of claims 1 to 5.
7. An application of the Au@CuS modified MOF material according to claim 6, characterized in that: The Au@CuS-modified MOF material is used as a gas-sensitive material to prepare a quartz crystal microbalance gas sensor.
8. A quartz crystal microbalance gas sensor, characterized in that: It comprises the Au@CuS modified MOF material as described in claim 6.
9. Use of the quartz crystal microbalance gas sensor according to claim 8 in detecting ammonia.
10. The use according to claim 9, characterized in that: During the ammonia detection process, the Au@CuS-modified MOF material was irradiated with 980nm infrared light.